2018
DOI: 10.1101/219980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information synergy: adding unambiguous quality information rescues social information use in ants

Abstract: Animals have access to many alternative information sources when making decisions, such as private information (e.g. memory) and social information. Social insects make extensive use of social information. However, when intentional social information (e.g. pheromone trails in ants) conflicts with private information (e.g. route memories), insects often follow their private information. Why is this? We propose that an asymmetry in the type of information provided by these two information sources drives the negl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
3
8
0
Order By: Relevance
“…Light levels have a large effect on the way in which L. niger foragers make use of, and deposit, pheromone trails. As previously reported [19,22,30], when route memories (private information) and pheromone trails (social information) conflict in bright light (3200 lux), L. niger foragers mostly follow their route memories. However, we found that as light levels decreased to dusk-like levels (10 lux) and on to darkness (0.0007 lux), the rate at which ants relied on private information decreased, until in darkness over half the ants chose to follow a pheromone-marked branch.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Light levels have a large effect on the way in which L. niger foragers make use of, and deposit, pheromone trails. As previously reported [19,22,30], when route memories (private information) and pheromone trails (social information) conflict in bright light (3200 lux), L. niger foragers mostly follow their route memories. However, we found that as light levels decreased to dusk-like levels (10 lux) and on to darkness (0.0007 lux), the rate at which ants relied on private information decreased, until in darkness over half the ants chose to follow a pheromone-marked branch.…”
Section: Discussionsupporting
confidence: 60%
“…Here, we study the use and provision of social information under different light levels in the ant Lasius niger . Under high light levels, L. niger preferentially follow private route memories over pheromone trails, even if the pheromone trails are very strong [22,30]. We first test confirm that route memories in L. niger are based solely on visual cues (as reported by [36]).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Camponotus fellah ants perform at a similar level with ~75-90% correct choices for the rewarded odour after The clear preference for the olfactory modality in conflict situations may give the impression that ants use their private information in a hierarchical way. Hierarchical information use has been suggested for private and social information (Almeida et al 2018), although it is clear that when choosing social or private information, information use strategies are more complex, as environmental conditions or other available information sources affect information use choices (Czaczkes et al 2018;Grüter and Leadbeater 2014;Jones et al in press). The preference found for the olfactory modality is likely strongly linked to the ecology of the investigated species.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an ant can shift to a new food source if it is of better quality than the currently exploited food (Czaczkes et al 2018). Yet, not only the energetic value of a food source is important, but also its other properties.…”
Section: Value Perceptionmentioning
confidence: 99%